Upaya Meningkatkan Hasil Belajar Matematika Peserta Didik Melalui Model Pembelajaran Discovery Learning di Kelas III SDN 03/X Tanjung Solok Semester Ganjil T.A 2021/2022 - Aisyah Aisyah (Journal on Education, 2022)
This study aims to describe and obtain information on improving mathematics learning outcomes through the Discovery Learning learning model. This research is classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were the thirds’ grade students of SDN 03/X Tanjung Solok, totaling 13 people. This research was conducted in the odd semester of the 2020/2021 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results showed that through the Discovery Learning learning model, the thirds’ grade students of SDN 03/X Tanjung Solok could improve their mathematics learning outcomes by giving praise.